2018
DOI: 10.1037/ppm0000167
|View full text |Cite
|
Sign up to set email alerts
|

The addictive potential of television binge watching: Comparing intentional and unintentional binges.

Abstract: This study proposes media audiences engage in 2 types of TV binge watching: intentional and unintentional. Using the differential susceptibility to media effects model as a framework, we draw from research on sensitivity theory and uses and gratifications to test whether unintentional binges are more likely to result in addiction symptoms, and whether this is due to impulsivity as a personality trait. Using an online survey, we find (a) most of our sample has engaged in both types of binge watching, (b) addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 45 publications
4
86
0
3
Order By: Relevance
“…Thus, higher scores of impulsivity were associated with both loss of control over binge-watching (as assessed with the s-IAT bingewatching and the BWES) and neglect of duties (BWES). In line with this, Riddle et al [24] recently reported that impulsivity is associated with unintentional binge-watching. Our results extend those findings as we found that impulsivity makes individuals not only vulnerable to loss of control over binge-watching, but also to continue binge-watching at the expense of duties.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, higher scores of impulsivity were associated with both loss of control over binge-watching (as assessed with the s-IAT bingewatching and the BWES) and neglect of duties (BWES). In line with this, Riddle et al [24] recently reported that impulsivity is associated with unintentional binge-watching. Our results extend those findings as we found that impulsivity makes individuals not only vulnerable to loss of control over binge-watching, but also to continue binge-watching at the expense of duties.…”
Section: Discussionmentioning
confidence: 60%
“…High impulsive individuals tend to have difficulties to focus on tasks, behave on impulse without thinking, and are less likely to think about or plan for the future [22]. Preliminary findings with regard to binge-watching suggest that trait impulsive behaviour (assessed with the Barratt-Impulsiveness Scale [23]) is associated with binge-watching [24]. Similarly, Orosz et al [25] administered the UPPS Impulsive Behavior Scale [26] and found that higher impulsivity scores were associated with obsessive feelings with regard to binge-watching.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reasons for the popularity of this practice and binge watching can be intentional and planned or unintentional (Riddle et al 2017). Motivations for binge watching are varied.…”
Section: The Practice and Impacts Of Binge Watchingmentioning
confidence: 99%
“…Pikul (2014) argues that binge watching has a negative physical effect, causing lethargy due to sitting for prolonged periods of time. Riddle et al (2017) examined the risks of addiction to binge watching, finding that unintentional binging was associated with addiction symptoms such as increased impulsivity, displacement of other behaviors, and continued viewing. This research also suggested the need to further examine how (or if) binge watching changes common media effects such as cultivation and desensitization.…”
Section: The Practice and Impacts Of Binge Watchingmentioning
confidence: 99%
“…Automaticity has been described as an impulsive process with integrated reward mechanisms that will transform watching series from a goal-directed behavior to automatic or habitual behavior. Initial studies reported a relationship between BW and impulsivity (Orosz et al, 2016;Riddle et al, 2018), which is a prominent risk factor for excessive and addictive behaviors such as internet gaming disorder (e.g. Ko et al, 2014).…”
Section: Introductionmentioning
confidence: 99%